Expansão do direito penal e criminalidade moderna: a observação das organizações criminosas na contemporaneidade com ênfase na corrupção e o reforço da diferenciação sistêmica do direito penal mediante os novos papeis do Ministério Público, a colaboração premiada e a pena privativa de liberdade - Porto, Pedro Rui da Fontoura (Universidade do Vale do Rio dos Sinos, 2020)
The Expansion of Criminal Law, from the perspective of Systems Theory, can be sustained as the natural and predictable response of the criminal legal system to the expectations of the social environment, concerning to the protection, including criminal, of social interests transcendent to the exclusive personal sphere, especially those synthetically unified in the concept of economic or modern criminal law. The increase in the complexity of social relations imposes the updating of meaning and the selective pressure for the establishment of new relationships between system and medium, maintaining the differentiation between both. The phenomenon, proper of post-modernity, has problematized the relations between Law and Politics, to the extent that it represents an advance of the latter, in the framework of a more regulatory democracy. The Expansion, especially in Brazil, is also consistent with the greater autonomy of the Public Prosecution Service which, to the same extent that it has achieved greater complexity and internal organization, increased its distinction with the Judiciary on behalf of endogenous choices for the defense of these new socioeconomic interests, through instruments of systemic observation such as plea bargaining, whose insertion, in the Brazilian criminal procedure system is justified as a consequence of international directives, inspired by common law, which replace the exclusive adversarial criminal procedure for another model of cooperation between the State and indicted that emphasizes the bargaining system. The Expansion has become notorius in Brazil, even more in the face of an Economic Criminality sector in which the relations between Law and Politics become more problematic: corruption. It is precisely in this area of modern crime that the autonomy of the Public Prosecutor’s Office and the plea bargaining have been leading a systemic Expansion, whose legitimacy has been more harshly questioned, especially by the application, increasingly frequent, of freedom deprivation of high figures in the political and economic system. Such a finding, possible even at international level, imposes an inquiry into the validity of the application of Criminal Law in terms of economic crime or, at least, the imposition of its most radical consequence: the penalty deprivation of liberty. At this point, the impropriety of Criminal Law for the confrontation of Economic Criminality was sustained, since the flexibility of guarantees, so peculiar to modern Criminal Law, is not compatible with the freedom restrictions. However, the economic analysis of the Law demonstrates that the economic offender is a calculation agent who decides reasonably through the comparison between the advantages of the illegal activity and the risks punishment. Therefore, only the freedom deprivation increase the distinction of the criminal justice system compared to other legal systems and emerges as suitable to produce sufficient countermotivation to economic criminality.
Keywords: Teoria dos sistemas; Expansão do direito penal; Ministério Público; Colaboração premiada; Pena privativa da liberdade; Systems theory; Expansion of criminal law; Public prosecution service; Plea bargaining; Penalty deprivation of liberty; ACCNPQ::Ciências Sociais Aplicadas::Direito